Navigating English-mediated online discourse: Communication strategies of Indonesian EFL learners in online discussions - Lestari, Ika Wahyuni; Andiansyah, Mahardhika (Politeknik Negeri Bali, 2024)
For non-native English speakers, effective and meaningful communicationin English can pose challenges due to potential limitations in their communicativecompetence. Such challenges can cause communication breakdowns if not effectivelymanaged. This complexity is compounded when English communication occurs in anonline setting, where technological issues and lack of social presence may disrupt thecommunication. This study aims to explore the communication strategies utilized byIndonesian EFL learners when participating in online group discussions. The data werecollected from six groups of first-year English Department students involving a total oftwenty-two students engaged in 20-minute online discussions per group. The analysisfocused on the discourse produced by the participants during these discussionsobserving the strategies employed by the participants. The findings indicated thatIndonesian EFL learners predominantly applied achievement and compensatorystrategies. These strategies encompassed code-switching, circumlocution,approximation, the use of all-purpose words, word foreignizing, and appealing for help.Among these strategies, code-switching emerged as the prevailing strategy forIndonesian EFL learners engaged in online group discussions. While conversing, code-switching was automatically and naturally used, particularly when referring toIndonesian acronyms and names. At last, implications and future directions areaddressed.